2004
DOI: 10.1021/ic049728x
|View full text |Cite
|
Sign up to set email alerts
|

Novel One-Dimensional Polymers Generated fromp-Ferrocenylbenzoate:  Syntheses, Structures, and Magnetic Properties

Abstract: Treatment of p-ferrocenylbenzoate [p-HOOCH4C6Fc, Fc = (eta5-C5H5)Fe(eta5-C5H5)] with Mn(OAc)2 x 2H2O or Cd(OAc)2 x 2H2O afforded one-dimensional linear chain polymer [[Mn(OOCH4C6Fc)2(mu2-OH2)(H2O)2](H2O)]n (1), double-bridge polymer [Mn(mu2-OOCH4C6Fc)2(phen)]n (phen = phenanthroline) (2), and ladderlike framework [[Cd(mu2-OOCH4C6Fc)(eta2-OOCH4C6Fc)(bbp)](CH3OH)]n (bbp = 4,4'-trimethylene-dipyridine) (3). The solution-state cyclic voltammograms indicate that the half-wave potentials of the ferrocenyl moieties i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 63 publications
(27 citation statements)
references
References 76 publications
3
24
0
Order By: Relevance
“…To the best of our knowledge, there are only three 1D compounds with a similar core that have been structurally and magnetically characterized. [21,22,24] As can be seen in Table 6, the analogous compound with a bpy ligand, [Mn(bpy)(3-ClC 6 H 4 COO) 2 ] n , [21] shows similar structural parameters and J value to those of 4, which is indicative of the minor effect of the basicity of the terminal ligands. However, changing the bridging ligands from chlorobenzoato to chloroacetato as in [Mn(ClCH 2 COO) 2 -(phen)] n [22] leads to a modification of the Mn-O distances and hence the J value.…”
Section: Magnetic Measurementsmentioning
confidence: 81%
See 3 more Smart Citations
“…To the best of our knowledge, there are only three 1D compounds with a similar core that have been structurally and magnetically characterized. [21,22,24] As can be seen in Table 6, the analogous compound with a bpy ligand, [Mn(bpy)(3-ClC 6 H 4 COO) 2 ] n , [21] shows similar structural parameters and J value to those of 4, which is indicative of the minor effect of the basicity of the terminal ligands. However, changing the bridging ligands from chlorobenzoato to chloroacetato as in [Mn(ClCH 2 COO) 2 -(phen)] n [22] leads to a modification of the Mn-O distances and hence the J value.…”
Section: Magnetic Measurementsmentioning
confidence: 81%
“…The manganese ions are bridged by two carboxylate ligands coordinated in a syn-anti mode, with a Mn···Mn distance of 4.546 Å, which is slightly longer than that reported for the analogous compound with 2,2Ј-bypiridine (4.515 Å) [21] but in the range of distances reported for other 1D compounds with a [Mn(µ 1,3 -RCOO) 2 ] n core (4.515-4.852 Å). [21,22,[24][25][26][27][28][29][30][31][32][33] There are two different Mn-O distances: the shortest distances (2.091 Å) correspond to O syn , while the largest distances (2.200 Å) correspond to O anti . The O syn atoms are trans to a N phen atom, while the O anti atoms are trans to the other O anti atoms.…”
Section: (Phen)] N (4)mentioning
confidence: 99%
See 2 more Smart Citations
“…[7] To the best of our knowledge, only three papers have been published on manganese complexes with ferrocene-involving carboxylate groups as ligands. [8][9][10] Among them, only the study reported by Hou, et al includes some investigation of the magnetic properties of the manganese complex with a p-ferrocenylbenzoato ligand. [9] In the other two cases, Tian, et al [8] and Kondo et al [10] described the redox properties of a dinuclear complex cation [Mn 2 (phen) 4 …”
Section: Introductionmentioning
confidence: 99%